Biocompatible silver nanoparticles from apricot kernel skin: a green synthesis approach to antibacterial and antiangiogenic therapies - Nejati, Omid; Torkay, Gulsah; Girgin, Ayca; Zaman, Buse Tugba; Akar, Remzi Okan; Giray, Betul; Ulukaya, Engin; Bakirdere, Sezgin; Bal-Ozturk, Ayca (SPRINGER INT PUBL AG, 2025)
Plant-based AgNPs synthesis has recently gained popularity due to its cost-effectiveness, feasibility, and environmentally friendly nature. In this study, we utilized apricot kernel skin extract for the first time as both a green reducing agent for silver ions and a stabilizing agent for the resulting AgNPs solution. This solution exhibited remarkable stability and biological activity. The biosynthesized AgNPs were characterized using several spectroscopic approaches. Particle size and zeta potential were found to be 145.5 +/- 62.02 nm and - 29.1 +/- 5.68 mV, respectively. The dynamic light scattering findings revealed a low polydispersity index of 0.229, indicating that the monodispersity distribution in solution is mainly single-sized and uniform species. The TEM image indicated that the AgNPs were spherical. Even 3 months after synthesis, AgNPs were stable. The DPPH test demonstrated that AgNPs have moderate antioxidant activity. Furthermore, depending on the dose, it is found to have high antibacterial activity against different bacterial species. It was also discovered that AgNPs, which are highly biocompatible with red blood cells in terms of hemolysis activity assay, were more lethal to non-small cell metastatic lung cancer epithelial cells (H1299) than human lung bronchial epithelial cells (Beas2B) with an LC50 of 6.03 and 14.19 mu g/mL, respectively, after 24 h treatment. At TGI concentration, AgNPs also significantly reduced H1299 cell migration. According to artificial intelligence analyses acquired from in ovo chorioallantoic membrane testing, AgNPs, which hold great potential for application in anticancer drug delivery systems, have been also found to reduce angiogenesis at low concentrations.
Keywords: Silver nanoparticles; Green synthesis; Apricot kernel skin extract; CAM assay; GOLD NANOPARTICLES; EXTRACT; ANGIOGENESIS; ANTIOXIDANT; GENERATION; AGNPS; Chemistry